2021
DOI: 10.1039/d0ra08756d
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of protein emulsion stability through glycosylated black bean protein covalent interaction with (−)-epigallocatechin-3-gallate

Abstract: Stability improvement of emulsions stabilized by covalent conjugation with glycosylated black bean protein and EGCG (BBPI-G–EGCG) was studied through structure changes of proteins and emulsion properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The results were presented as the mean ± standard deviation using Microsoft Excel 365. The statistical comparisons were performed using one-way analysis of variance (ANOVA) and the independent sample ttest (with the level of significance at p values < 0.05) [48].…”
Section: Discussionmentioning
confidence: 99%
“…The results were presented as the mean ± standard deviation using Microsoft Excel 365. The statistical comparisons were performed using one-way analysis of variance (ANOVA) and the independent sample ttest (with the level of significance at p values < 0.05) [48].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that a simultaneous combination of MD and RA may be more effective in preventing droplet aggregation (FL or CL) during storage (Yadav et al, 2010). The addition of hydrophilic MD and polyphenols enhanced the affinity between proteins and water molecules, making them form a relatively tight interface membrane on oil drop surface and, thus, effectively avoiding droplet aggregation and enhancing storage stability of emulsions (Wang et al, 2021).…”
Section: Storage Stabilitymentioning
confidence: 99%
“…Microwave modification and alkaline polyphenol covalent modification can possibly promote each other to improve the stability of soy protein emulsions and form emulsions with a smaller average particle size and more stable performance. Wang et al [ 21 ] showed that the covalent modification of EGCG and glycosylated black soybean protein could further reduce the average particle size of black soybean protein emulsions. The results of this study are similar to the average particle size of soy protein emulsions modified by this method.…”
Section: Resultsmentioning
confidence: 99%
“…The interfacial protein adsorption (AP) of soy protein emulsions modified in different ways is shown in Table 1 . After microwave treatment, the interfacial protein adsorption of the MSPI emulsion increased significantly ( p < 0.05), possibly because the structure of soy protein is unfolded by microwave modification, which exposes more hydrophobic groups and makes the soy protein have a better hydrophobic balance, which results in more protein molecules adsorbing on the oil–water interface, increasing the interfacial protein adsorption [ 21 ]. After covalent binding with ferulic acid (FA), the interfacial protein adsorption of the SPI-FA (AM) emulsion increased from 40.27 ± 0.65% to 69.67 ± 2.52%, which can be attributed to the introduction of polyphenol changing the molecular conformation of proteins, making more protein molecules adsorb on the surface of oil drops more quickly, increasing the protein content at the emulsion interface, increasing the thickness of the oil–water interface film in the emulsion, and enhancing emulsion stability [ 12 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%